New Common Coupled Coincidence Point Theorems for Generalized Weakly Contraction Mappings with Applications to Dynamic Programming - Sumalai, Phumin; Kumam, Poom; Khaofong, Chatuphol; Martinez-Moreno, Juan (Communications in Mathematics and Applications, 2018)
In this paper, we define a new concept of generalized weakly contraction mapping for coupled common fixed points in the space of the bounded function. We also prove the existence and uniqueness theorems for common coupled fixed points. As an application of our result, we also study the problem of existence and uniqueness of solutions for a class of system of functional equations which appears in dynamic programming.